Effect of Steel Fiber on First-Cracking Behavior of Ultra-High-Performance Concrete: New Insights from Digital Image Correlation Analysis - Xing Lu; Lei Tu; Chengjun Tan; Hua Zhao (Buildings)
The first-cracking behavior of ultra-high-performance concrete (UHPC) is critical for the functionality and durability of its structures. However, determining the first-cracking strength by the linear limit point is challenging due to the nonlinear behavior before the initial crack. This study utilizes an improved Digital Image Correlation (DIC) technique to detect cracks and directly determine the first-cracking strength. The effect of steel fiber length, volume fraction, diameter, and shape on the first-cracking behavior was evaluated through direct tensile testing. Results indicate that incorporating steel fibers can enhance the first-cracking strength of UHPC to varying extents, ranging from 26.07% to 121.31%. Specifically, the length and volume fraction of steel fibers significantly affect the first-cracking strength, whereas the diameter and shape have minimal impact. The shape of steel fibers can influence the initial crack pattern due to stress concentration in deformed fibers. On the other hand, the inclusion of steel fibers can also negatively impact the first-cracking strength due to the introduction of air voids. Finally, considering both the positive and adverse effects of steel fibers, an updated predictive model for the first-cracking strength is proposed based on regression analysis of the experimental data. The proposed model can accurately predict the first-cracking strength of UHPC, fitting well with the existing data.